An Investigation of the Emotional Balance Inventory - Thackerson, Emery K.; Jones, Ian T.; Baker, Megan E.; Grice, James W. (Advances in Social Sciences Research Journal, 2022)
Using experience sampling methodology, this study investigated the scaling format and validity of an alternative affect measure, the Emotional Balance Inventory (EBI). Signaling occurred twice per day for a week, directing undergraduate students (n = 79) to report the frequencies of their emotions using either a dichotomized or Likert scaled format of the EBI. At the conclusion of the daily ratings, participants completed two measures of psychological well-being. Results revealed little evidence in the distinction of the response formats, and there was marginal evidence supporting the monotonic relationship between the affect measure and psychological well-being measures. External validity and generalizability are discussed, along with implications for future research utilizing clinical populations.